2020
DOI: 10.1088/1674-4926/41/12/122802
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive study of crystalline AlN/sapphire templates after high-temperature annealing with various sputtering conditions

Abstract: High-quality AlN/sapphire templates were fabricated by the combination of sputtering and high-temperature (HT) annealing. The influence of sputtering parameters including nitrogen flux, radio frequency power, and substrate temperature on the crystalline quality and surface morphology of annealed AlN films were investigated. With lower substrate temperature, lower power, and lower N2 flux, the full width at half maximum of the X-ray rocking curve for AlN (0002) and (10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…To date, several groups, including ours, have reported the fabrication of FFA Sp-AlN. [34][35][36][37][38] Most have utilized an Al metal target for the sputtering deposition. In addition, we have reported that controlling the polarity of the FFA Sp-AlN by using different target materials is possible.…”
Section: Overview Of Ffa Sp-alnmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several groups, including ours, have reported the fabrication of FFA Sp-AlN. [34][35][36][37][38] Most have utilized an Al metal target for the sputtering deposition. In addition, we have reported that controlling the polarity of the FFA Sp-AlN by using different target materials is possible.…”
Section: Overview Of Ffa Sp-alnmentioning
confidence: 99%
“…Moreover, the final crystalline quality of the FFA Sp-AlN strongly depends also on the initial crystalline quality of Sp-AlN, which is determined by sputtering deposition conditions (e.g. substrate temperature, chamber pressure, and sputtering gas species) 38,43) and AlN film thickness. 23,25,35,36,39,40) The influence of the sputtering deposition conditions, film thickness, and annealing conditions on the crystallinity of FFA Sp-AlN are discussed in the next section.…”
Section: Overview Of Ffa Sp-alnmentioning
confidence: 99%
“…The background pressure of the sputtering chamber was below 3.2 × 10 –5 Pa. Two kinds of working gases were employed for comparation: pure N 2 or N 2 –O 2 gas mixture. The N 2 flow rate was set to 100 sccm, which was low to ensure a longer mean free path of particles and less tilt component of AlN . As for the latter, 1 sccm O 2 was supplied throughout the sputtering process and meant to regulate the polarity.…”
Section: Methodsmentioning
confidence: 99%
“…The N 2 flow rate was set to 100 sccm, which was low to ensure a longer mean free path of particles and less tilt component of AlN. 27 As for the latter, 1 sccm O 2 was supplied throughout the sputtering process and meant to regulate the polarity. The deposition rates were similar (∼0.21 nm/s) due to the negligible effect of trace O 2 on the yield and the collision possibility of the ejected Al particles.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…14,15) Great efforts have been made to improve the quality of AlN grown on sapphire. High-temperature annealing (HTA) [16][17][18][19] probably is the most effective way to reduce the TDD. AlN films with TDDs about 2 × 10 8 cm −2 were acquired by HTA.…”
mentioning
confidence: 99%